The Islamic Governance Law on Environmental Conservation in Sinjai Regency - Junaid, Bismar; Jayadi, Ahkam; Natsif, Fadli Andi; Singh, Prasad; Hamsir, (Alauddin Law Development Journal, 2024)
This study aims to assess the preservation of the environment in Sinjai Regency in the perspective of Islamic Constitutional Law (siyasah syariah). The focus of the study includes: 1) the role of local governments in maintaining environmental conservation, 2) factors that influence its implementation, and 3) Environmental Conservation Review according to Islamic law. This study uses a qualitative descriptive approach with formal juridical methods and normative Syar'i based on the Qur'an. Data collection techniques include observation, interview, and documentation, analyzed through classification, verification, and conclusion. The results showed that the Local Government, through the Department of Environment, has implemented various environmental conservation programs. The supporting factor is competent human resources, while the obstacle is the lack of budget. In addition, the lack of involvement of public and religious figures in socialization causes environmental jurisprudence to be neglected, despite its importance in the face of the current ecological crisis.